2022
DOI: 10.1037/pspi0000367
|View full text |Cite
|
Sign up to set email alerts
|

Rehumanizing the self after victimization: The roles of forgiveness versus revenge.

Abstract: Everyday maltreatments can threaten people's basic sense of being human. Can victims restore their sense of humanness after it has been damaged by an offense and, if so, how? Four studies compared forgiving and taking revenge as responses to victimization. In Study 1, participants recalled a time they either forgave or took revenge against someone who had hurt them. In Studies 2 and 3, they imagined being victimized by a coworker and then either forgiving or taking revenge against him. In Study 4, they wrote e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 109 publications
(194 reference statements)
5
26
0
Order By: Relevance
“…It follows that one remedy may be “rehumanization,” and, according to the precepts of the Interpersonal Theory of Suicide among other accounts of human suffering and flourishing, key leverage points include social connection (as antidote to thwarted belonging) and a sense of meaning and mattering (as opposed to perceived burdensomeness) (Joiner, 2005). Rehumanization through forgiveness has been shown to reduce desire toward self‐harm, create a greater sense of belonging to the human community, and increase the importance of one's moral identity (Schumann & Walton, 2022). Small doses of connection and mattering—perhaps via behavioral activation platforms that incentivize socializing and causes and activities to which one wants to contribute—accrue and compound, with potential to mitigate purging, suicide risk, and other clinical problems as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that one remedy may be “rehumanization,” and, according to the precepts of the Interpersonal Theory of Suicide among other accounts of human suffering and flourishing, key leverage points include social connection (as antidote to thwarted belonging) and a sense of meaning and mattering (as opposed to perceived burdensomeness) (Joiner, 2005). Rehumanization through forgiveness has been shown to reduce desire toward self‐harm, create a greater sense of belonging to the human community, and increase the importance of one's moral identity (Schumann & Walton, 2022). Small doses of connection and mattering—perhaps via behavioral activation platforms that incentivize socializing and causes and activities to which one wants to contribute—accrue and compound, with potential to mitigate purging, suicide risk, and other clinical problems as well.…”
Section: Discussionmentioning
confidence: 99%
“…and, according to the precepts of the Interpersonal Theory of Suicide among other accounts of human suffering and flourishing, key leverage points include social connection (as antidote to thwarted belonging) and a sense of meaning and mattering (as opposed to perceived burdensomeness) (Joiner, 2005). Rehumanization through forgiveness has been shown to reduce desire toward self-harm, create a greater sense of belonging to the human community, and increase the importance of one's moral identity (Schumann & Walton, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the generalized compensation belief, their acts could receive permission or at least a remission of punishment from observers (who are the majority of people in any social movement), creating new chains of ill acts in society. According to religious teachings and psychological findings (e.g., Davis et al, 2021;Loeffler et al, 2018;Schumann & Walton, 2022), when facing maltreatment and suffering, it is more efficacious and adaptive to treat these experiences as an opportunity to mature and grow rather than ruminating on the negative experience. Our findings suggest that such an expectation may contradict a natural moral belief people tend to hold, despite that it could still be an ideal for people to strive for.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Rehumanization occurs when the target holds no grudge against the perpetrator and is ready to forgive the perpetrator. Schumann and Walton (2021) found that targets who could forgive have unique humane qualities. Thus, victims sense of humaneness can be restored on account of the dehumanizing process by the perpetrator.…”
Section: Ahimsa At the Social Context Of Work Is A Conscious Actionmentioning
confidence: 99%
“…The inclination among scholars and practitioners to imbibe a collaborative climate stimulates research on a rehumanizing response behaviour (Kay and Skarlicki, 2020; Holm, 1996) so that it does not lead to further conflict escalation (Andersson and Pearson, 1999). Studies have shown that victims who forgive their perpetrators feel more rehumanized than those who seek revenge (Schumann and Walton, 2021). Forgiveness is also indirectly associated with job satisfaction and organization citizenship behaviours (Fehr and Gelfand, 2012).…”
Section: Introductionmentioning
confidence: 99%